Chimeric protein repair of laminin polymerization ameliorates muscular dystrophy phenotype - McKee, Karen K. (J Clin Invest, 2017)
Mutations in laminin α2-subunit (Lmα2, encoded by LAMA2) are linked to approximately 30% of congenital muscular dystrophy cases. Mice with a homozygous mutation in Lama2 (dy2J mice) express a nonpolymerizing form of laminin-211 (Lm211) and are a model for ambulatory-type Lmα2-deficient muscular dystrophy. Here, we developed transgenic dy2J mice with muscle-specific expression of αLNNd, a laminin/nidogen chimeric protein that provides a missing polymerization domain. Muscle-specific expression of αLNNd in dy2J mice resulted in strong amelioration of the dystrophic phenotype, manifested by the prevention of fibrosis and restoration of forelimb grip strength. αLNNd also restored myofiber shape, size, and numbers to control levels in dy2J mice. Laminin immunostaining and quantitation of tissue extractions revealed increased Lm211 expression in αLNNd-transgenic dy2J mice. In cultured myotubes, we determined that αLNNd expression increased myotube surface accumulation of polymerization-deficient recombinant laminins, with retention of collagen IV, reiterating the basement membrane (BM) changes observed in vivo. Laminin LN domain mutations linked to several of the Lmα2-deficient muscular dystrophies are predicted to compromise polymerization. The data herein support the hypothesis that engineered expression of αLNNd can overcome polymerization deficits to increase laminin, stabilize BM structure, and substantially ameliorate muscular dystrophy.